Evidence-based vaccinology: supporting evidence-informed considerations to introduce routine hepatitis A immunization in South Africa - Patterson, Jenna (Department of Public Health and Family Medicine, 2023)
Hepatitis A is a vaccine preventable disease caused by the Hepatitis A Virus (HAV). Currently, South Africa is classified by the World Health Organization (WHO) as a high hepatitis A endemic region where 90% of children are assumed to be “naturally immunised” following HAV exposure before the age of 10 years old. In high hepatitis A endemic settings, routine vaccination against HAV is not necessary due to high rates of “natural immunization”. Recent data suggest a possible shift from high to intermediate HAV endemicity may be occurring in South Africa. Countries with intermediate HAV endemicity and no routine hepatitis A vaccination program have a high risk of experiencing hepatitis A outbreaks and high costs associated with care. Currently, there is no routine vaccination program against HAV in South Africa. The aim of this PhD was to generate evidence for decision making on whether a routine vaccination program against HAV should be considered for introduction into the South African Expanded Program on Immunizations (EPI-SA). The objectives included gathering context-specific evidence on the epidemiologic features of hepatitis A, clinical characteristics of the disease, hepatitis A vaccine characteristics and cost of case management. Using this evidence, the PhD estimated the future epidemiology of hepatitis A and impacts of routine hepatitis A vaccination scenarios in the country. The PhD's overall methods were informed by the principles of Evidence-Based Vaccinology for developing vaccine recommendations. The project included a mixed-methods approach: systematic reviews, a retrospective clinical folder review, mathematical modelling, and economic evaluation. A dynamic transmission model was built to forecast the future epidemiology of hepatitis A and to simulate the impacts of several different childhood hepatitis A vaccination strategies in South Africa. Selected findings have been published in relevant peer-reviewed journals. In addition, a technical dossier was prepared to submit to the South African National Advisory Group on Immunization (NAGI) on behalf of the Hepatitis A Working Group for considerations of introducing hepatitis A vaccination into the South African EPI.